Laomenes albonigrus sp. nov., (Crustacea: Decapoda; Pontoniinae) from Ashmore Reef, Western Australia - Bruce, A. J. (Zootaxa, 2014)
One specimen of an un-described species of pontoniine shrimp of the genus Laomenes Clark, 1919, Laomenes albonigrus sp. nov., was collected from a crinoid host from Ashmore Reef, Western Australia, and is now described and illustrated.